Molecular study of TNF-α, IL-1B and IL-10 genes in Eris Covid-19 patients - Ammer Mohammed; Nazar Mohammed; Khalied zakair (Microbes and Infectious Diseases, 2025)
Background: The combination between exposure to T. gondii parasite and COVID-19 infection developed as an important focusing of the present study. Aim: This study aims to investigate the polymorphisms of TNF-α, IL-1B and IL-10 genes in Eris Covid-19 patients associated with Toxoplasmosis. Methods: This study included (100) patients (52 males and 48 females) infected with Eris (EG.5) Virus, whose ages ranged from (11 to >55) years. The study samples were collected from Al-Numan Hospital in Baghdad City during the period from July 2024 to August 2025. The study also included (50) apparently healthy individuals (25 males and 25 females) whose ages ranged from (11 and >50) as a control group. Results: The levels of IL-10 (pg/ml) was higher among patient with  T. gondii  IgM levels >1 (IU/ml) than T. gondii IgM levels <1 (IU/ml) with (10.59±2.18, 10.40±2.47), with a non-significant difference (P=0.77), while the levels of TNF-α (pg/ml) was higher among T. gondii IgM levels <1 (IU/ml)  than T. gondii  IgM levels >1 (IU/ml) with (19.37±8.41, 13.79±4.96) respectively, with a significant difference (P= 0.002). Conclusion: The results revealed there were a highly levels of TNF, IL-1ß and IL-10 concentrations with Eris Coved 19 co-infection with Toxoplasmosis. Also, the results found a variation occurrence in IL-1β, IL-10 and TNFα genes.